PTSD & Post-PTSD Comparative Psychoanalysis of 'Charlie' from The Perks of Being a Wallflower and 'Naoko' from Norwegian Wood - Ahmed, Nobel; Marjan, Sumaeta; Alam, Asibul (Universitas Airlangga, 2024)
PTSD or post-traumatic stress disorder is a serious mental condition that some people develop after a shocking, terrifying, or dangerous event which are mostly known as traumas. After a trauma, it is common to struggle with fear, anxiety, and sadness. Most people get better with time, but PTSD thoughts and feelings do not fade away completely. In the novels The Perks of Being a Wallflower (1999) by Stephen Chbosky and Norwegian Wood (1987) by Haruki Murakami the characters Charlie and Naoko respectively, are observed to go through traumas due to childhood memories, complicated sexual relationships, and death of dear ones. Their post PTSD period has taken place in certain conditions which gave somewhat different endings to their stories denoting different components of personality as per the representation of Sigmund Freud’s theory of personality. According to Freud, id works on pleasure principle, super ego on the moral side and ego balances both id and superego of human psychology. This study is an exploration of Charlie and Naoko’s PTSD and their relationships throughout their lifetime to bring out the comparative personality of the characters in their post PTSD period though the theory of Freud. The paper has been carried out through qualitative research of close textual analysis and comparative and contrastive methods of study.